Are aposematic signals honest? A review. (4th July 2015) - Summers, K.; Speed, M. P.; Blount, J. D.; Stuckert, A. M. M.
Abstract: We explore the relevance of honest signalling theory to the evolution of aposematism. We begin with a general consideration of models of signal stability, with a focus on the Zahavian costly signalling framework. Next, we review early models of signalling in the context of aposematism (some that are consistent and some inconsistent with costly honest signalling). We focus on controversies surrounding the idea that aposematic signals are handicaps in a Zahavian framework. Then, we discuss how the alignment of interests between signaller and predator influences the evolution of aposematism, highlight the distinction between qualitative and quantitative honesty and review theory and research relevant to these categories. We also review recent theoretical treatments of the evolution of aposematism that have focused on honest signalling as well as empirical research on a variety of organisms, including invertebrates and frogs. Finally, we discuss future directions for empirical and theoretical research in this area.